2019
DOI: 10.2141/jpsa.0180052
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Supplementation of Mixed Yeast Culture Derived from <i>Saccharomyces cerevisiae</i> and <i>Kluyveromyces maxianus</i>: Effects on Growth Performance, Nutrient Digestibility, Meat Quality, Blood Parameters, and Gut Health in Broilers

Abstract: This study aimed to evaluate the effect of dietary supplementation of a mixed yeast culture (MYC; Saccharomyces cerevisiae YJM1592 and Kluyveromyces maxianus TB7258 in a 1:1 ratio) on growth performance, nutrient digestibility, meat quality, blood parameters, and gut health of broiler chickens. In total, 576 one-day-old male broilers (Ross 308) with an average initial body weight (BW) of 37±0.51 g were used in a 35-day experiment with a completely randomized design. The broilers were randomly assigned to 3 die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
17
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 31 publications
3
17
1
Order By: Relevance
“…A combination of yeastderived carbohydrates and probiotics increased BWG of pullets (Yitbarek et al, 2015). Yang et al (2018) reported that Lactobacillus plantarum had antibacterial activity and affected nutrient digestibility, whereas β-glucan and chitin content in Saccharomyces cerevisiae inhibited the growth of pathogenic bacteria in the intestine (Anwar et al, 2017), and improved the intestinal health (Sun & Kim, 2019).…”
Section: Tasj-30494_revised By Authormentioning
confidence: 99%
“…A combination of yeastderived carbohydrates and probiotics increased BWG of pullets (Yitbarek et al, 2015). Yang et al (2018) reported that Lactobacillus plantarum had antibacterial activity and affected nutrient digestibility, whereas β-glucan and chitin content in Saccharomyces cerevisiae inhibited the growth of pathogenic bacteria in the intestine (Anwar et al, 2017), and improved the intestinal health (Sun & Kim, 2019).…”
Section: Tasj-30494_revised By Authormentioning
confidence: 99%
“…The addition of YC at 2.5 g/kg activates macrophages, thereby increasing lysozyme content in the serum of laying hens, thus contributing to their resistance of pathogenic bacteria and enhancing their immunity ( Gao et al, 2008 ). Further, studies have also reported that this immunity induced by YC is passed on to offspring and reduces symptoms of coccidiosis infection ( Lu et al, 2019 ; Sun and Kim, 2019 ). In addition, some previous studies have shown that YC administration positively affects poultry laying performance and intestinal health ( Zhang J.C. et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Dietary YC supplementation in sows increased the milk lactose, protein and DM content, and changed the fecal microbiota of sows, resulting in improved growth performance of piglets [ 9 , 10 ]. Sun et al [ 11 ] reported that mixed yeast culture supplementation increased body weight gain, digestibility of dry matter, and population of Lactobacillus in broilers. These results suggest that yeast and yeast products have important effects on intestinal health and microbial flora.…”
Section: Introductionmentioning
confidence: 99%